2018
DOI: 10.1038/pr.2018.47
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index and risk of intraventricular hemorrhage in preterm infants

Abstract: BackgroundIntraventricular hemorrhage (IVH) and pre-pregnancy obesity and underweight have been linked to inflammatory states. We hypothesize that IVH in preterm infants is associated with pre-pregnancy obesity and underweight due to an inflammatory intrauterine environment.MethodsPopulation-based study of infants born between 22 and 32 weeks' gestation from 2007 to 2011. Data were extracted from vital statistics and the California Perinatal Quality Care Collaborative. Results were examined for all cases (any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Our findings are consistent with studies conducted in Sweden, which also find that maternal overweight and obesity during pregnancy is associated with an increased risk for PTB, especially VPTB [23]. In addition to the increased risk of PTB and VPTB conferred by abnormal BMI, it has also been shown that for those infants born preterm, abnormal BMI confers a higher risk of morbidities associated with PTB compared to preterm infants born to women with normal BMI [47,48].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with studies conducted in Sweden, which also find that maternal overweight and obesity during pregnancy is associated with an increased risk for PTB, especially VPTB [23]. In addition to the increased risk of PTB and VPTB conferred by abnormal BMI, it has also been shown that for those infants born preterm, abnormal BMI confers a higher risk of morbidities associated with PTB compared to preterm infants born to women with normal BMI [47,48].…”
Section: Discussionsupporting
confidence: 91%